Cooperative OFDM Underwater Acoustic Communications - Cheng, Xilin; Yang, Liuqing; Cheng, Xiang (Wireless Networks, 2016)
Following underwater acoustic channel modeling, this book investigates the relationship between coherence time and transmission distances. It considers the power allocation issues of two typical transmission scenarios, namely short-range transmission and medium-long range transmission. For the former scenario, an adaptive system is developed based on instantaneous channel state information. The primary focus is on cooperative dual-hop orthogonal frequency division multiplexing (OFDM). This book includes the decomposed fountain codes designed to enable reliable communications with higher energy efficiency. It covers the Doppler Effect, which improves packet transmission reliability for effective low-complexity mirror-mapping-based intercarrier interference cancellation schemes capable of suppressing the intercarrier interference power level. Designed for professionals and researchers in the field of underwater acoustic communications, this book is also suitable for advanced-level students in electrical engineering or computer science.